PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERBASIS CONTEXTUAL TEACHING AND LEARNING (CTL) MATERI SISTEM PERSAMAAN LINEAR TIGA VARIABEL SISWA KELAS X MIA SMAN 9 KOTA JAMBI - Endah Fitria; Buyung Buyung; Aisyah Aisyah (PHI: Jurnal Pendidikan Matematika, 2018)
Abstract: This research is motivated by the existence of problems in the preparation of LKS being used in SMA Negeri 9 Kota Jambi. LKS is a teaching material that also plays an important role in improving the quality of learning. Preparation of the appropriate LKS and in accordance with the curriculum used is expected to achieve the learning objectives, so it needs continuous LKS development activities. The purpose of this research is to develop LKS based on Contextual Teaching and Learning (CTL) on linear equation system material three valid, practical and effective variables.This type of research development is Research and Development (R & D) with the ADDIE development model. Stages of the ADDIE development model consist of analysis, Design, Development, Implementation, Evaluation. The research instrument consists of Questionnaire and question instrument. Questionnaires consist of validation sheet by the material expert, validation assessment sheet by design expert, validation assessment sheet by media expert, individualized trial evaluation sheet, small group trial evaluation sheet, and evaluation field test sheet. while the question instrument consists of a pre-test and post-test questions. LKS developed, then validated by the validator. Validation results obtained LKS with revisions based on suggestions and comments validator. Validity is illustrated by the percentage of material expert, designer and media experts in 82,61% in "highly valid" category, 76,16% in "valid" category, 90% in "very valid" category. LKS was then piloted into three stages: individual trials with 3 medium and low-skilled students, small group trials with 6 students, and field trials conducted in the real classroom of class X MIA 2 with 34 students. Judging from the comparison of pre-test and post-test values obtained tcount of 15.37 and ttable of 2.03 then tcount > ttable stated there are significant differences. Based on the results of validation, test and test results of learning then obtained the results of research that shows the feasibility of LKS with CTL approach pertained in categories valid, practical and effective.Keywords: Student Worksheet, Contextual Teaching and Learning, the development model of ADDIE